2011
DOI: 10.1016/j.febslet.2011.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin stimulates MMP-9 expression, de-regulates the MMP-9/TIMP-1 equilibrium and promotes MMP-9 dependent invasion in human MDA-MB-231 breast cancer cells

Abstract: Keywords:Breast cancer Thioredoxin Matrix metalloproteinase-9 MMP-9/TIMP-1 equilibrium NF-jB Invasion a b s t r a c t Increased expression of thioredoxin (Trx)-1 and matrix metalloproteinase (MMP)-9 associates with malignant breast cancer progression. Here, we describe a functional relationship between Trx-1 and MMP-9 in promoting MDA-MB-231 breast cancer cell invasive behaviour. Trx-1 overexpression stimulated MMP-9 expression, de-regulated the MMP-9/TIMP-1 equilibrium and augmented MMP-9 involvement in a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…17) In contrast, the deregulation of the MMP-9/ TIMP-1 equilibrium has facilitated the invasion of human MDA-MB-231 breast cancer cells. 25) In the present study, we demonstrated that p-cymene transcriptionally augments the production of TIMP-1 in TPA-stimulated HT-1080 cells, under which the invasiveness of HT-1080 cells was attenuated. Thus, these results suggest a possible mechanism in that the antitumor invasive activity of p-cymene includes not only the down-regulation of MMP-9 production but also the up-regulation of TIMP-1 production.…”
Section: Discussionsupporting
confidence: 55%
“…17) In contrast, the deregulation of the MMP-9/ TIMP-1 equilibrium has facilitated the invasion of human MDA-MB-231 breast cancer cells. 25) In the present study, we demonstrated that p-cymene transcriptionally augments the production of TIMP-1 in TPA-stimulated HT-1080 cells, under which the invasiveness of HT-1080 cells was attenuated. Thus, these results suggest a possible mechanism in that the antitumor invasive activity of p-cymene includes not only the down-regulation of MMP-9 production but also the up-regulation of TIMP-1 production.…”
Section: Discussionsupporting
confidence: 55%
“…Extracellular thioredoxin has been suggested to have chemotactic activity and to act as chemo-attractant for neutrophils, monocytes and Tcells [24]. Extracellular thioredoxin has also been associated with cancer cell metastasis [25] and the promotion of a matrix metalloproteinase-9 (MMP-9) dependent invasive phenotype in malignant breast cancer cells [26].…”
Section: Subcellular Localisation and Functions Of Thioredoxinmentioning
confidence: 99%
“…Thioredoxin enhances the invasive behavior of tumor cells by regulating MMP activity, which is required for ECM degradation [25,26]. HIF-1 over-expression during hypoxia has also been associated with ECM degradation by upregulating MMP-2 [94] and MMP-9 gene expression [95].…”
Section: The Interaction Of Redox and Hypoxic Pathways Under Intermitmentioning
confidence: 99%
“…8 In addition, Trx upregulated the protease MMP-9 via NFκB, facilitating tumor cell invasion. 27 In fact, distinct subcellular localizations of Trx were already described for cancer as compared with normal tissues in other tumor entities. 28,29 In gallbladder carcinomas, patients with nuclear Trx showed shorter survival than patients without nuclear Trx.…”
Section: Discussionmentioning
confidence: 95%